2006
DOI: 10.1086/500675
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Fine Structure of Electricity Prices*

Abstract: Birkbeck ePrints: an open access repository of the research output of Birkbeck College http://eprints.bbk.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
224
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(232 citation statements)
references
References 28 publications
8
224
0
Order By: Relevance
“…We denote by F := (F t ) t≥0 the filtration generated by (B t ) t≥0 and augmented by P-null sets. As in [7], the spot price of electricity X follows a standard time-homogeneous Ornstein-Uhlenbeck process with positive volatility σ , positive adjustment rate θ and positive asymptotic (or equilibrium) value μ; i.e., X x is the unique strong solution of Note that this model allows negative prices, which is consistent with the requirement to balance supply and demand in real time in electrical power systems and also consistent with the observed prices in several electricity spot markets (see, e.g., [12,18]). We denote by the random time of a consumer's demand for electricity.…”
Section: Problem Formulationsupporting
confidence: 70%
“…We denote by F := (F t ) t≥0 the filtration generated by (B t ) t≥0 and augmented by P-null sets. As in [7], the spot price of electricity X follows a standard time-homogeneous Ornstein-Uhlenbeck process with positive volatility σ , positive adjustment rate θ and positive asymptotic (or equilibrium) value μ; i.e., X x is the unique strong solution of Note that this model allows negative prices, which is consistent with the requirement to balance supply and demand in real time in electrical power systems and also consistent with the observed prices in several electricity spot markets (see, e.g., [12,18]). We denote by the random time of a consumer's demand for electricity.…”
Section: Problem Formulationsupporting
confidence: 70%
“…Finally, Knittel and Roberts (2005) find an inverse leverage effect for electricity prices in the United States. Other studies have found similar results (see, for example, Weron 2006Weron , 2008Harris 2006;Geman and Roncoroni 2006;Koopman et al 2007;Pilipović 2007;Sotiriadis et al 2016).…”
Section: The Electricity System Price For the Nordic Spot Electricitysupporting
confidence: 65%
“…Financial models use historical price series, and assuming stationarity, we can extract reliable characteristics for both the mean and volatility. Spot electricity prices exhibit high volatility, strong mean reversion (see, for example, Lucia and Schwartz 2002;Geman and Roncoroni 2006), frequent spikes and seasonal patterns (see Higgs and Worthington 2008;Huisman and Mahieu 2003;Thomas et al 2011) and differ from region to region (Li and Flynn 2004). Moreover, Goto and Karolyi (2004) find a mean-reversion effect with seasonal changes in volatilities as well as volatility clustering for electricity trading hubs in the United States, Australia and the Nordic/Baltic market.…”
Section: The Electricity System Price For the Nordic Spot Electricitymentioning
confidence: 99%
“…In contrast, a jump regime switching model was developed in [7], which uses the hypothesis that log spot price switches between multiple linear Gaussian processes with a constant one period transition probability matrix. A regime switching threshold is also used by Geman and Roncoroni in [8] and [9] to force negative jumps if the price exceeds the threshold value. The authors in [8] claim that this model structure captures both trajectorial and statistical properties of US electricity price data well.…”
Section: Introductionmentioning
confidence: 99%